Single-Wall Carbon Nanotube-Coated Cotton Yarn for Electrocardiography Transmission - Yuliang Zhao (Micromachines, 2018)
We fabricated a type of conductive fabric, specifically single-wall carbon nanotube-coated cotton yarns (SWNT-CYs), for electrocardiography (ECG) signal transmission utilizing a “dipping and drying” method. The conductive cotton yarns were prepared by dipping cotton yarns in SWNTs (single-wall carbon nanotubes) solutions and then drying them at room temperature—a simple process that shows consistency in successfully coating cotton yarns with conductive carbon nanotubes (CNTs). The influence of fabrication conditions on the conductivity properties of SWNT-CYs was investigated. The results demonstrate that our conductive yarns can transmit weak bio-electrical (i.e., ECG) signals without significant attenuation and distortion. Our conductive cotton yarns, which combine the flexibility of conventional fabrics and the good conductivity of SWNTs, are promising materials for wearable electronics and sensor applications in the future.